2022
DOI: 10.3390/atmos13111799
|View full text |Cite
|
Sign up to set email alerts
|

A Short Review of Simple Analytical Methods for the Evaluation of PAHs and PAEs as Indoor Pollutants in House Dust Samples

Abstract: Studies on indoor air quality are indispensable when considering that people spend approximately 85% of their time in confined environments. This short review mostly takes into consideration research that uses passive samplers to evaluate the quality of indoor environments (houses, school, cars, etc.). This short review summarizes most analytical methods to detect and quantify PAHs and PAEs in house dust used as a passive sampler. The objective of house dust analysis is to identify the presence, amount and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Trace analysis presents critical issues due to analytical blank problems [23][24][25]. For this purpose, all the materials (instruments, glassware, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…Trace analysis presents critical issues due to analytical blank problems [23][24][25]. For this purpose, all the materials (instruments, glassware, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…24 Samples of unknown high concentration should be initially checked on a GC (FID detector) or GC (ECD detector) of the same chromatography before analysis to prevent contamination of the GC-MS system by high concentration organics. 31…”
Section: Quality Controlmentioning
confidence: 99%
“…Studies have found their widespread distribution in different environmental matrices, such as indoor environments (houses, schools, cars, etc.) and sediments from an open-pit mining area [ 4 , 5 ]. It has been well established that PAHs have detrimental biological effects, such as mutagenicity, toxicity, and carcinogenicity, posing a serious threat to human health [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%